Pengaruh Kecerdasan Emosional, Motivasi Kerja, Lingkungan Kerja dan Budaya Organisasi terhadap Kinerja Guru Sekolah Dasar Negeri di Kecamatan Malinau Barat Kabupaten Malinau - Lesperi Lesperi; Nurul Hidayat (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Teacher performance in remote areas often faces structural and psychological challenges that may hinder instructional effectiveness. In Malinau Barat District, limited infrastructure, work pressure, and organizational dynamics potentially influence teachers’ professional outcomes. This study aims to examine the effects of emotional intelligence, work motivation, work environment, and organizational culture on the performance of public elementary school teachers. The research employed a quantitative explanatory design using a survey method. Data were collected from 86 teachers selected through proportional random sampling from a population of 109 teachers. A Likert-scale questionnaire consisting of 50 items was administered and tested for validity and reliability prior to analysis. Multiple linear regression analysis was applied after fulfilling classical assumption tests. The findings reveal that emotional intelligence, work motivation, work environment, and organizational culture each have a positive and statistically significant effect on teacher performance, both partially and simultaneously. The coefficient of determination (R² = 0.73) indicates that 73% of the variance in teacher performance is explained by the four independent variables. These results highlight the importance of strengthening both internal competencies and organizational conditions to enhance educational quality in remote primary schools.